(untitled) (Research, Society and Development, 2020)
AVF has great benefits for the patient, greater durability, low rate of infection and thrombosis, promotes freedom of movement and action, safer access, the disadvantages it causes are: extremity ischemia, low spasm flow, partial or partial venous thrombosis total, appearance of aneurysm and bruising. The object of this study is the knowledge of the nurse and his team with Button puncture in arteriovenous fistula. With Objectives: To identify the knowledge of the nurse and his nursing team about the buttonhole technique for puncture in the AVF and Describe the role of the nurse and his team in handling and training about the buttonhole technique. This is a qualitative field research carried out at a hemodialysis center in Rio de Janeiro. The participants were the nursing team. Twenty professionals participated in the research, being 05 (five) nurses and 15 (fifteen) nursing technicians. From the analysis of the participants’ testimonies, the following categories originated: Team Knowledge, Team Training and Team Perceptions about the advantages associated with the use of the technique. It is hoped that this study can bring and produce a reflection and a different narrative on the subject addressed, understanding that patients who undergo hemodialysis treatment have a significant improvement in their quality of life.